Gender differences in heart rate responses to different types of physical activity in physical education classes - J. Sarradel; E. Generelo; J. Zaragoza; J.A. Julián; A. Abarca-Sos; B. Murillo; A. Aibar (Asociación Española de Ciencias del Deporte, 2011)
The purpose of this study was to investigate gender differences in children's physical activity levels during physical education (PE) classes. Specific attention was paid to differences between genders in the heart rate responses to different types of activities in PE classes. Activity levels were assessed by monitoring continuous heart rates, with results indicating that girls were significantly more active during PE than boys. Team sports in both sexes, and tennis in the case of the girls, fulfil the recommendations to occupy at least 50% of PE class time doing moderate and vigorous physical activities (MVPA). The results suggest that structured PE classes may provide different amounts of physical activity for both genders. Key Words: adolescent, health promotion, moderate and vigorous activity.